Observational study on early pulmonary complications following emergency abdominal surgeries in a tertiary care hospital in West Bengal - Anirban Hazra,; Yogesh Chauhan,; Premangshu Ghosh,; Riddhisundar Samanta,; Mohan Pradhan,; Subhabrata Das, (Asian Journal of Medical Sciences, 2025)
Background: Emergency surgeries account for half of all surgical deaths and one-third of all complications. Post-operative outcomes following emergency abdominal surgery are generally worse leading to different serious consequences and post-operative pulmonary complication (PPC) is one of the most common among them (incidence rate: 20–50%). The consequences of developing a PPC are serious with doubled health-care costs, longer hospital stays, and higher mortality rates when compared to elective surgery. Aims and Objectives: This study was done to estimate the incidence of early post-operative pulmonary complications, the influence of pre-existing pulmonary morbidity and related factors in the development of PPC; and the outcome of management of PPC. Materials and Methods: In this institution-based observational descriptive study, a total of 122 patients, who presented to the surgery emergency room and underwent emergency abdominal surgery (April 2021–May 2022), were followed up for the development of PPCs. The cure/complication rate after management was also assessed. Results: In this study incidence of PPC was around 39%, which is similar to the highest reported figures in other studies. Among PPCs most common PPC came out to be atelectasis (58%). Pre-operative pulmonary comorbidity, upper or upper versus lower abdominal incision, duration of operation, indication for operation, and type of anesthesia all influence the risk for PPC in this setting (P<0.05). Conclusions: The incidence of PPCs in this study is quite high. Pre-existing pulmonary comorbidities, incision sites above the umbilicus, general anesthesia, and prolonged duration of operation all significantly impact the development of PPC.